2019
DOI: 10.21608/ejrsa.2019.3684.1057
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Histopathologic Evaluation of L-Carnitine and vitamin E Efficacy on Irradiated Jaw Bones

Abstract: combination on irradiated jaw bones in rats through radiographic assessment of the bone density and histopathologic examination of bone morphology. Forty male albino rats were divided randomly into 4 groups each of 10 rats. Group R represented the rats that received fractionated radiation dose (2 Gray per fraction) for one week. Groups LR, eR and LeR represented the rats that received L-Carnitine 300mg/kg via intra peritoneal injection, vitamin e 40mg/kg via intramuscular injection or both daily for five days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…This observation is consistent with He et al , who found destroyed osteocytes in radioactively damaged bone tissues and justified this by IR reducing osteocyte viability and increasing cell apoptosis [ 35 ]. Our observation is also consistent with Amira et al , who demonstrated that γ-radiation causes decreased bone cells, osteoblastic resorption, and loss of bone thickness [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with He et al , who found destroyed osteocytes in radioactively damaged bone tissues and justified this by IR reducing osteocyte viability and increasing cell apoptosis [ 35 ]. Our observation is also consistent with Amira et al , who demonstrated that γ-radiation causes decreased bone cells, osteoblastic resorption, and loss of bone thickness [ 36 ].…”
Section: Discussionsupporting
confidence: 93%